2007
DOI: 10.1071/aj06005
|View full text |Cite
|
Sign up to set email alerts
|

Longtom—confirmation of a New Play in Offshore Gippsland

Abstract: The Longtom gas field was discovered in 1995, when the Longtom–1/ST1 wildcat well in the northern part of the offshore Gippsland Basin encountered dry gas in tight sandstones towards the base of the Latrobe Group, in what is now called the Admiral Formation of the Emperor Subgroup. In 2004 the Longtom–2/ST1 exploration well confirmed significant vertical and lateral extension of these prospective gas sands, and also provided very encouraging production test and core data. The recent Longtom–3 wells have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, the successful pooling of hydrocarbons in fault traps is problematic within the study area although possible, as has been demonstrated in the Flounder Field (ESSO, 1988). Other exceptions exist in the Golden Beach and Emperor Subgroups as have been demonstrated in the Kipper and Longtom Fields (Lanigan et al, 2007;Sloan et al, 1992).…”
Section: Implications For Petroleum Explorationmentioning
confidence: 99%
“…Thus, the successful pooling of hydrocarbons in fault traps is problematic within the study area although possible, as has been demonstrated in the Flounder Field (ESSO, 1988). Other exceptions exist in the Golden Beach and Emperor Subgroups as have been demonstrated in the Kipper and Longtom Fields (Lanigan et al, 2007;Sloan et al, 1992).…”
Section: Implications For Petroleum Explorationmentioning
confidence: 99%